TINGKAT ADOPSI TANAM JAJAR LEGOWO 2:1 PADA PETANI PADI DI KABUPATEN PURWAKARTA - Bambang Sunandar; Hepi Hapsari; Lies Sulistyowati (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Jajar legowo 2:1 planting system is an innovation in rice plants that can increase rice crop productivity by increasing plant population by adjusting plant spacing. The dissemination of these innovations has been done a lot through government programs, but in the last five years rice productivity in Purwakarta Regency is still low and the application of the innovation of jajar legowo 2:1 planting is still low. This study aims to determine the level of adoption of the jajar legowo 2:1 planting innovation in Purwakarta Regency. This study uses quantitative design with survey methods. The number of respondents was 130 people taken through a propotional random sampling. Data were analyzed using descriptive analysis. The results showed tha the adoption rate of farmers to the innovation of jajar legowo 2:1 in Purwakarta Regency at the knowledge stage was 63.1% (high), the persuasion stage 58.8% (moderate), the decision making stage 85.4% (very high), the implementation phase was 43.8% (moderate), and the confirmation stage was 64.1% (high).